Lower Affinity T Cells are Critical Components and Active Participants of the Immune Response - Martinez, Ryan J.; Evavold, Brian D. (Frontiers in Immunology, 2015)
Kinetic and biophysical parameters of T cell receptor (TCR) and peptide:MHC (pMHC) interaction define intrinsic factors required for T cell activation and differentiation. Although receptor ligand kinetics are somewhat cumbersome to assess experimentally, TCR:pMHC affinity has been shown to predict peripheral T cell functionality and potential for forming memory. Multimeric forms of pMHC monomers have often been used to provide an indirect readout of higher affinity T cells due to their availability and ease of use while allowing simultaneous definition of other functional and phenotypic characteristics. However, multimeric pMHC reagents have introduced a bias that underestimates the lower affinity components contained in the highly diverse TCR repertoires of all polyclonal T cell responses. Advances in the identification of lower affinity cells have led to the examination of these cells and their contribution to the immune response. In this review we discuss the identification of high- versus low-affinity T cells as well as their attributed signaling and functional differences. Lastly mechanisms are discussed that maintain a diverse range of low- and high-affinity T cells.